The Role of Taxation in Addressing Inequality A Literature Analysis.docx - Nurwanah, Andi (Advances in Taxation Research, 2024)
Purpose: This study aims to explore the role of taxation in addressing economic inequality, focusing on progressive tax systems and their effectiveness in redistributing wealth and mitigating disparities. Research Design and Methodology: The research employs a qualitative literature analysis, synthesizing insights from seminal works, empirical studies, and cross-country comparisons. Key sources include Piketty's "Capital in the Twenty-First Century," Saez and Zucman's research on tax evasion, and various OECD and UNU-WIDER studies. Findings and Discussion: The analysis reveals that well-designed progressive tax systems are crucial for reducing economic inequality. Piketty's findings highlight the effectiveness of high marginal tax rates in decreasing wealth concentration. Saez and Zucman underscore the importance of robust tax enforcement to combat evasion. Cross-country comparisons show that countries with progressive tax structures and substantial social spending, such as the Scandinavian nations, achieve lower levels of inequality. However, challenges remain in developing economies, where tailored approaches to tax compliance and administration are necessary. Implications: The study underscores the need for policymakers to design and implement progressive tax policies effectively. This includes closing tax loopholes, enhancing compliance, and integrating tax policies with broader social measures. International cooperation is essential to address tax evasion and avoidance. The research provides valuable insights for designing equitable tax systems that can promote social equity and economic stability.